Radiologic Results and Hearing Preservation With a Straight Narrow Electrode via Round Window Versus Cochleostomy Approach at Initial Activation. Issue 6 (July 2015) - Hassepass, Frederike; Aschendorff, Antje; Bulla, Stefan; Arndt, Susan; Maier, Wolfgang; Laszig, Roland; Beck, Rainer
Abstract : Objective: To evaluate the potential influence of two different cochlear implant (CI) electrode carrier approaches to the scala tympani in terms of insertion depth and angle as well as hearing preservation. Study Design: Retrospective follow-up study. Setting: Tertiary care academic center. Patients: Forty-one adult subjects underwent cochlear implantation using the Cochlear Nucleus CI 422 slim straight electrode (Cochlear Limited, New South Wales, Australia) with the intent of achieving atraumatic electrode insertion and hearing preservation. Interventions: Fourteen subjects were implanted using a cochleostomy approach and 27 via a round window approach. Main Outcome Measures: Radiologic assessment of insertion depth and angle was performed on postoperative rotational tomography. Postoperative low-frequency hearing preservation, complete loss of residual low-frequency hearing, and speech perception in quiet measures were obtained in defined intervals for both groups. Results: Mean insertion depth reached 21.5 mm (standard deviation, 1.1), whereas mean insertion angle of 388 degrees (standard deviation, 34.7) was revealed for all CI recipients, with no significant difference between the cochleostomy cohort and the round window cohort. The CI-aided speech perception in quiet showed significantly higher scores 3 to 4 months after activation compared with the preoperative speech perception results. The audiologic data demonstrated no statistically significant difference in probability of complete loss of residual low-frequency hearing at initial activation between the cochleostomy group and the round window group. Conclusion: The present results suggest that similar insertion depth and angle as well as similar low-frequency hearing preservation can be achieved in cochlear implantation with this straight narrow electrode via either cochleostomy approach or round window approach at least at initial activation. This fact gives the surgeon the opportunity to adapt access to the scala tympani as needed. Abstract : Supplemental digital content is available in the text.